Idiopathic restrictive cardiomyopathy is part of the clinical expression of cardiac troponin I mutations - Mogensen, Jens (American Society for Clinical Investigation, 2003)
Restrictive cardiomyopathy (RCM) is an uncommon heart muscle disorder characterized by impaired filling of the ventricles with reduced volume in the presence of normal or near normal wall thickness and systolic function. The disease may be associated with systemic disease but is most often idiopathic. We recognized a large family in which individuals were affected by either idiopathic RCM or hypertrophic cardiomyopathy (HCM). Linkage analysis to selected sarcomeric contractile protein genes identified cardiac troponin I (TNNI3) as the likely disease gene. Subsequent mutation analysis revealed a novel missense mutation, which cosegregated with the disease in the family (lod score: 4.8). To determine if idiopathic RCM is part of the clinical expression of TNNI3 mutations, genetic investigations of the gene were performed in an additional nine unrelated RCM patients with restrictive filling patterns, bi-atrial dilatation, normal systolic function, and normal wall thickness. TNNI3 mutations were identified in six of these nine RCM patients. Two of the mutations identified in young individuals were de novo mutations. All mutations appeared in conserved and functionally important domains of the gene.